Family functionality and nutritional status in children aged 1 to 5 years in a rural area of Huánuco, Peru - Shirley Angela, Osorio Rumi (2024)
Objective. To determine the influence of family functionality on the nutritional status of children aged 1 to 5 years in a rural area of Huánuco (Peru) in 2023. Methods. The study was observational, cross-sectional, prospective, and analytical, with an explanatory level. The sample consisted of the census population, made up of 106 heads of families with their youngest child, aged 1 to 5 years. The Family APGAR Scale was used to measure family functionality, and the anthropometric chart was used to measure nutritional status. Fisher's test was applied for hypothesis testing. Results. The majority of participants perceived a family functionality of 86.8% (92), followed by those representing family dysfunctionality of 13.2% (14). It was also observed that most had an appropriate height for their age 47.2% (50), normal weight for age values 66.0% (70), and normal weight for height values in 68.9% (73). Conclusions. Family functionality influences the nutritional status of children aged 1 to 5 years in a rural area of Huánuco, in 2023.